PENGUATAN PROGRAM ACARA DAKWAH RADIO DAIS MASJID AGUNG JAWA TENGAH DI ERA MODERN - Kholid_Noviayanto, Kholid Noviyanto (JKaKa:Jurnal Komunikasi dan Konseling Islam, 2023)
Di era modern, media komunikasi menjadi pusat perhatian manusia. Mengkaji problematika manusia saat ini, yang ditandai dengan minimnya filter atas globalisasi telah muncul pola kehidupan yang hedonis, minimnya kepedulian terhadap agama, dan kenakalan remaja. Menjawab persoalan tersebut, maka salah satu upaya telah dilakukan oleh pengelola radio DAIS adalah membuat inovasi program siaran radio, berbasis kajian dakwah Islam. Oleh karenanya, hal ini mendasari tujuan peneliti untuk mengungkap inovasi program siaran dakwah yang dilakukan oleh pengelola radio DAIS. Penelitian ini menggunakan metode kualitatif agar dapat mengungkap secara mendalam tentang inovasi program yang dilakukan oleh pengelola radio DAIS dengan pendekatan difusi inovasi. Hasil penelitian tersebut menunjukkan bahwa inovasi penguatan program mata acara radio DAIS meliputi program penataan hati manusia, penguatan syariat Islam, tadabbur Al Quran, serta penguatan akhlak bagi remaja yang disiarkan melalui pemancar lokal,dan dapat diakses secara streaming, melalui dais play. Kata Kunci : Penguatan, Program Acara, Radio DAIS, Pusaran Hedonisme. Abstract Radio has the power to persuade humans, especially in this Modern era, communication media is the center of human attention. Examining human problems in this modern era, which is characterized by the loss of filters over globalization of all aspects, has given birth to hedonistic patterns of life, neglect of religion, and the emergence of juvenile delinquency. Answering this problem, one of the efforts made by DAIS radio is to innovate radio broadcast programs in addition to being tone-patterned, also based on Islamic proselytizing studies that innovate based on public analysis of media access, one of which is DAIS radio. Therefore, this underlies the researcher's goal to uncover the innovation of the da'wah broadcast program carried out by the DAIS radio manager. Methodologically, this type of research is qualitative with the intention of wanting to reveal more in-depth about program innovations carried out by DAIS radio managers with an innovation diffusion approach . The results showed that the innovation of the DAIS radio program in the form of strengthening Islamic programs includes structuring the human heart, strengthening Islamic law, deepening of the Quran, as well as strengthening morals for adolescents packaged in the da'wah study program through an innovation process and diffusing to DAIS radio listeners both through local transmitters, streaming, and android applications in the form of dais play . This innovation generated a significant response from listeners. Keywords : Reinforcement, Program Events, DAIS Radio, Maelstrom of Hedonism.